Sedekah Online Yusuf Mansur: Otoritas dan Bahasa Agama di Media Sosial - Hidayat, Mansur (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2018)
The study explained religious authority in social media by exploring on online alms dakwah delivered by Yusuf Mansur (YM). The problems were how the online dakwah by Yusuf Mansur delivered through social media and how far online alms of Yusuf Mansur has the authority to be followed. The research purposed to find out the way YM constructs authority and language of religion on social media in alms dakwah and learn how far YM authority is followed by the audience. In addition, the study is used to understand the role of social media in philanthropy activities. The study referred to four months of online and offline ethnographic fieldwork toward activity related to YM online alms on social media. Results show that the YM alms dakwah was a focus on the layer of authority: self-presentation, switching code, and textual reference. These three things were useful to reinforce the legitimacy of message of YM online alms dakwah as well as efforts to keep the existence of social media. While the message of dakwah was communicated by linked on material rewards. These efforts were able to strengthen audience believe in alms, but the audience with a different ideology tend to selective in receiving messages.